Pengaruh Leverage dan Investasi terhadap Nilai Perusahaan (Studi pada Perusahaan Makanan dan Minuman di Bursa Efek Indonesia) - Solikahan, Eka Zahra; Ratnawati, Kusuma; Djawahir, Achmad Helmy (Jurnal Aplikasi Manajemen, 2013)
This study was aimed to analyze the effect of leverage on firm value, the effect of leverage on investment, the effect of investment on firm value and effect of leverage on firm value through investment. The research was conducted in the food and beverage companies listed on the Indonesia Stock Exchange (BEI), consisted of 15 companies from 2007 through 2011. The analysis used was PLS (Partial Least Square). The study result showed that leverage variable influenced on the firm value, leverage didn't influence on the investment and investment variable influenced on the firm value but leverage didn't influence on the firm value through investment.